CLINICAL CHARACTERISTICS AND OUTCOMES OF CANCER PATIENTS REQUIRING INTENSIVE CARE UNIT ADMISSION: A PROSPECTIVE OBSERVATIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Advances in oncology and critical care have improved the survival of cancer patients; however, many still require intensive care unit (ICU) admission because of postoperative needs, disease-related complications, or treatment-associated adverse events. Data on the clinical characteristics and outcomes of critically ill cancer patients remain limited in developing countries. Materials and Methodology: This prospective observational study was conducted over one year in the ICU of a tertiary care teaching hospital in Gujarat, India. A total of 500 adult patients with confirmed solid or hematological malignancies requiring ICU admission were included. Demographic characteristics, cancer-related variables, indications for ICU admission, severity scores, ICU interventions, and outcomes were recorded. Factors associated with hospital mortality were analyzed using univariate analysis. Results: The mean age of the patients was 59.8 ± 13.6 years, and 59.0% were males. Solid tumors accounted for 91.0% of cases, while 46.0% had Stage IV disease. Gastrointestinal malignancies (29.0%) were the most common cancer type, followed by lung cancer (18.0%). Postoperative monitoring was the leading indication for ICU admission (55.0%), followed by sepsis/septic shock (16.0%) and acute respiratory failure (13.0%). Mechanical ventilation was required in 37.0% of patients, vasopressor support in 29.0%, and renal replacement therapy in 7.0%. ICU mortality was 16.0%, while hospital mortality was 21.0%. Advanced age, metastatic disease, recurrent or progressive malignancy, unplanned ICU admission, sepsis, acute respiratory failure, higher APACHE II and SOFA scores, mechanical ventilation, vasopressor requirement, and renal replacement therapy were significantly associated with hospital mortality (p